Wspominane, wyobrażone, przesunięte. Rosja i Francja w emigracyjnej korespondencji Zinaidy Gippius - Krycka-Michnowska, Iwona (Acta Neophilologica, 2021)
The topic of this article are the letters of Zinaida Gippius from 1920-1945, which permit one to read the images of Russia and France contained therein as the result of the emigration experience. The analysis of correspondence leads to the conclusion that emigration shapes the identity of the writer, who over the years begins to perceive France as her new home and new homeland. However, in creating her autobiographical place, Gippius does not limit herself to one model. In her correspondence permanently there is a tension between Russian and French fate. Next to the aforementioned and Bolshevik Russia there is the picture of a new, imaginary Russia: free, just, based on the principles of brotherhood.